Um conjunto de melhorias nos serviços de streaming de vídeo: Netflix, Globoplay e Amazon Prime Vídeo baseadas na percepção de seus usuários - Ribeiro, Elthon Ferreira (2022)
Video streaming services have become popular as an instrument for consuming audiovisual content in recent years. The objective of this study is to propose improvements to the video streaming services: Netflix, Globoplay and Amazon Prime Vídeo based on the perception of ten users. To achieve the result, qualitative research was carried out through bibliographic research to support the concepts of digital consumption, user perception, streaming, integration of streaming services and content unification. Then, the data collection that used ten semi-structured interviews and finally, the content analysis of the responses of the users of the services to verify the problems experienced as well as suggestions for improvements. The Netflix, Amazon Prime Vídeo and Globoplay streaming services need the following improvements: an increase in the number of accesses and the number of simultaneous screens per subscription; the reduction of the amount charged for subscribing to the services; improving the streaming interface so that the user can perform the desired actions efficiently; greater dissemination of new audiovisual productions in various communication channels and the improvement of their content.